Controlled synthesis of high-performance β-FeOOH anodes for lithium-ion batteries and their size effects. (April 2015) - Yu, Linghui; Wei, Chao; Yan, Qingyu; Xu, Zhichuan J.
Abstract: β-FeOOH has recently been reported to have a very high lithium storage capacity of 1400 mAh g −1, 20–40% higher than those widely reported for iron-based anodes, such as Fe2 O3 and Fe3 O4 . However, many properties of this material that are important for their use in lithium-ion batteries remain unknown. Here, we present a study on the effects of particle size on their lithium storage performance and the kinetics associated with the redox reactions. The study is based on β-FeOOH nanorods prepared by a simple hydrolysis method which is able to control the size of the rods in a wide range, diameter from tens of nanometers down to 5 nm. Three materials with different sizes, mean diameter 5, 13 and 53 nm, are investigated for lithium storage. They show a very high and comparative capacity at a low current density, but different initial Coulombic efficiencies and rate capabilities. The kinetic study reveals the initial size of the material influences the formation of the SEI layers on the material and has significant effects on the kinetics of the redox reactions that lead to different rate behaviors. This study provides fundamental information and understanding of β-FeOOH anodes for their further development. Graphical abstract: Highlights: A simple route to control the size of β-FeOOH nanorods over a wide range is presented. A size-effect study on β-FeOOH as anodes for LIBs is carried out for the first time. All the three β-FeOOH investigated show a very high capacity and rate capability. A kinetic study is performed to understand their different properties.